Investigation on influence of SiCp on three-body abrasive wear behaviour of glass/epoxy composites (Fracture and Structural Integrity, 2021)
The present study present the influence of SiCp incorporation on three-body abrasive wear behavior of glass/epoxy composites. The investigations was carried out using dry sand rubber wheel abrasive wear test apparatus. 2k factorial design of experiment was used to capture the experimental data. The parameters considered are abrading distance, load and speed. The wear volume loss  found to increase with the increasing values of wear parameters. The applied load has exhibited significant effect on volume loss. Incorporation of SiCp contributed to enhance wear resistance of glass/epoxy composites. The linear regression was also presented in the study to correlate abrasion parameters with wear volume loss. SEM image analysis of abraded surface revealed the occurrence of ploughing, micro-cutting, matrix removal and fiber breakage.
Keywords: Polymer Matrix Composites; Wear; Statistical model; Scanning Electron Microscopy